Arrangement of Office Interior Layout Designs Using Multifunctional Furniture in CV Archi Design Studio Home Offices Semarang - Hardianningrum, Ratna; Pratama, Alif Ilham (Architecture Study Program, Faculty of Engineering and Computer Science, Universitas Muhammadiyah Semarang, 2024)
Offices located in residential areas with limited land need more careful planning so that the office remains professional even though it is located in a residential area. The use of appropriate furniture needs to be arranged so that the office space can accommodate the activities of an office. Arranging space using multifunctional furniture is a solution to make maximum use of space. Designing multifunctional furniture that suits the function of the office space is very necessary so that the office looks neater and more beautiful it can increase the professionalism of the office. An office that is not well organized will reduce client confidence in the company's performance. This research aims to design multifunctional office furniture that can accommodate office activities in limited space to maximize the function of the space. This research method uses a qualitative method by collecting information, namely field surveys, literacy studies, and interviews at the CV Archi Design Studio limited land office in the city of Semarang. From the research results, the interior layout of the office was analyzed using multifunctional office furniture that was appropriate to the limited space. The results of this research are a recommendation for interior space layout design using multifunctional office furniture that is suitable for small office spaces. With this research, it can be concluded that it is important to organize a good office space by using the right multifunctional furniture so that the office looks neater, more beautiful, and more functional.